Three cases of BRAF-mutant melanoma with divergent differentiation masquerading as sarcoma - Cilento, Michael A; Kim, Chankyung; Chang, Sean; Farshid, Gelareh; Brown, Michael P (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
Melanoma is an important cause of skin cancer related death throughout the world, particularly in Europe, the United States, and Australia. Rarely melanoma undergoes divergent differentiation to simulate the full morphologic and immunohistochemical features of other malignancies, notably sarcoma. However, such cases retain the molecular signatures of melanoma, including BRAF gene mutations. Gene mutation analysis of tumour DNA, now standard practice for all melanomas of stage III or above, may establish the diagnosis of melanoma in some advanced malignancies of unknown lineage. A prior history of melanoma or risk factors for melanoma may be the first clue that an advanced malignancy represents metastatic melanoma. Recognition of this presentation of melanoma can allow a patient to access well-tolerated life-prolonging therapies such as targeted therapy, inhibiting the BRAF/MEK pathway, and immune checkpoint inhibitor therapy.